Waterborne polyurethane dispersion as well as preparation method and application thereof

By designing the aqueous polyurethane dispersion with core-shell structure, the self-assembly of hydroxyl prepolymer and hydrophobic prepolymer is used to form nanoparticles, which solves the problem of insufficient resistance of aqueous polyurethane adhesives under high temperature and humidity conditions, and significantly improves the glue The body strength and heat resistance of the adhesive.

CN119264363APending Publication Date: 2025-01-07HANGZHOU TRANSFAR FINE CHEM CO LTD +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411433727.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing water-based polyurethane adhesives have insufficient resistance under high temperature and humidity conditions and cannot meet the needs of use under extreme conditions.

Method used

A water-based polyurethane dispersion with core-shell structure was designed. By synthesizing two prepolymers and forming nanoparticles during emulsification, the hydroxyl prepolymer segments are self-assembled to form shells, and the hydrophobic prepolymers form inner cores, which enhance the isocyanate. The bonding efficiency of the type curing agent forms a three-dimensional network structure to improve molecular weight and performance.

Benefits of technology

The body strength, heat resistance and humidity resistance of the adhesive are significantly improved. After 72 hours of maintenance at 25℃, the glue opening length is only 1mm, and the 95% humidity test strip is fully opened for more than 168 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention designs a waterborne polyurethane dispersion as well as a preparation method and application thereof. In the synthesis process, a diamine chain extender containing hydroxyl is designed into a chain segment containing a hydrophilic group, the chain segment forms an outer layer of the nano particle during self-assembly, meanwhile, the chain segment without the hydrophilic group is designed to be distributed in the nano particle, and through the design, the hydroxyl in the chain segment can be distributed on the surface of the nano particle, so that the surface of the nano particle is protected; the reaction rate with the isocyanate curing agent is increased, so that a three-dimensional network structure is formed during use, the molecular weight is increased, the performance is improved, and the body strength, aging resistance and chemical resistance of the adhesive are improved. The adhesive containing the waterborne polyurethane dispersion has excellent bonding hand feeling, excellent later-stage high temperature resistance, excellent humidity and heat resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive preparation, and in particular relates to an aqueous polyurethane dispersion and a preparation method and application thereof. Background Art

[0002] Adhesives prepared from waterborne polyurethane dispersions do not harm workers or pollute the environment during use, which is in line with current international development trends and national policy orientations. Currently, waterborne polyurethane resins account for only 16% of polyurethane adhesives, and most polyurethane adhesives are still solvent-based polyurethanes. In the waterborne shoe adhesive industry, the currently available waterborne shoe adhesives can only meet the basic needs of ordinary shoemaking, and cannot meet the needs of scenes with high adhesive performance requirements under extreme conditions, such as labor protection shoes worn under high temperature operations, training shoes and outdoor sports shoes for outdoor wading or high humidity conditions.

[0003] Patent CN116199851A prepares a waterborne polyurethane adhesive by adding a diol with a side chain and partially capping the polymer to adjust the crystal sequence and molecular weight distribution of the polymer. The adhesive has good wettability and initial adhesion, but poor resistance to moisture and heat in the later stage. Patent CN114133533B modifies the waterborne polyurethane resin by adding a waterborne silane oligomer, which is a mixture of an aminosilane oligomer and an epoxysilane oligomer. The adhesive is prepared with the resin, which has good adhesion and water resistance, but the later high temperature resistance and moisture and heat resistance still need to be improved. Summary of the invention

[0004] The present invention aims to solve the problem that the existing waterborne polyurethane has poor high temperature resistance and moisture and heat resistance in the later stage, designs and synthesizes a waterborne polyurethane dispersion with a core-shell structure, synthesizes two prepolymers, and then emulsifies to form nanoparticles with a core-shell structure. During the emulsification process, the prepolymer 1 segment containing hydroxyl groups forms the outer shell of the nanoparticles during self-assembly, and the prepolymer 2 segment without hydrophilic groups forms the inner core of the nanoparticles. Through this design, the hydroxyl groups in the segments can be distributed on the surface of the nanoparticles, enhancing the binding efficiency with the isocyanate curing agent, thereby forming a three-dimensional network structure when used, increasing the molecular weight, and improving the performance. Therefore, the adhesive prepared by the dispersion of the present invention has more excellent bulk strength, heat resistance, and moisture and heat resistance. In certain embodiments of the present invention, prepolymer 1 and prepolymer 2 have the same main structure, the difference is that prepolymer 1 uses different chain extenders, wherein the chain extender used in prepolymer 1 is a hydroxyl-containing polyamine chain extender and a hydrophilic compound containing ionic groups or potential ionic groups, and the hydroxyl groups are present on the main chain of the polymer segment, and the hydrophobic prepolymer 2 has the same main structure as prepolymer 1, but the chain extender used does not contain hydroxyl groups and does not include hydrophilic compounds containing ionic groups or potential ionic groups.

[0005] One of the technical solutions of the present invention is to provide a method for preparing an aqueous polyurethane dispersion, the specific steps of which are as follows: 1) Prepolymer 1 and prepolymer 2 are mixed evenly to obtain a mixed solution, wherein the volume ratio of prepolymer 1 to prepolymer 2 is 1:1.2-1:0.6; the main chain of the prepolymer 1 has a hydroxyl group, and the prepolymer 2 is hydrophobic; 2) Add water to the above mixture and shear and disperse it; 3) Separating the organic solvent and adjusting the solid content, an aqueous polyurethane dispersion can be obtained. The aqueous polyurethane dispersion is a nanoparticle with a core-shell structure. There are hydroxyl groups on the main chain of the polyurethane, and the hydroxyl groups are all located on the surface of the nanoparticle.

[0006] By preparing two polymers, a hydrophilic polymer and a hydrophobic polymer, when emulsified with water, the hydrophobic prepolymer 2 is located inside through self-assembly, thereby causing all hydroxyl groups of the prepolymer 1 to face outwards, which is convenient for reaction with the curing agent.

[0007] Furthermore, the method for preparing the prepolymer 1 in step 1 comprises the following steps: 1) Component S1, component S2, and component S7 are mixed uniformly and reacted at 75-85°C for 2-6h until the NCO% of the system reaches the theoretical value to obtain an isocyanate-terminated prepolymer; 2) The isocyanate-terminated prepolymer system obtained in step 1 is cooled to 50°C, and then component S8 is added to dissolve and dilute, followed by adding components S3 and S4, reacting at 30-45°C for 5-20min, and then adding component S5, and continuing to react at 30-45°C for 5-20min to obtain prepolymer 1.

[0008] Furthermore, the mixed system of components S1, S2 and S7 in step 1 includes S8; components S3 and S4 in step 2 are added to the system in the form of aqueous solutions, and the mass of water is 4-6 times the sum of the masses of components S3 and S4; component S5 is added to the system in the form of aqueous solutions, and the mass of water is 5-7 times the mass of component S5.

[0009] Further, the S1 is a polyisocyanate, including one or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate and dicyclohexylmethane diisocyanate, 8.0-20.0 parts by weight, preferably 10.0-18.0 parts by weight; The S2 is a macromolecular polyol having an average molecular weight of 500-5000 g / mol, including one or more of polyethylene glycol, polytetrahydrofuran ether glycol, polycaprolactone diol, polycarbonate diol, polyethylene adipate diol, polybutylene adipate diol, polyneopentyl adipate diol, and polyhexanediol adipate diol, in an amount of 68.0-85.0 parts by weight, preferably 70.0-85.0 parts by weight; The S3 is a hydrophilic compound containing an ionic group or a potential ionic group, which contains at least one group capable of reacting with isocyanate, including one or more of sulfonic acid type hydrophilic compounds, 1.0-5.0 parts by weight, preferably 2.0-3.0 parts by weight; The S4 is a polyamine small molecule chain extender containing at least one or more hydroxyl groups, including one of N-(2-hydroxypropyl)ethylenediamine and hydroxyethylethylenediamine, 0.5-4.0 parts by weight, preferably 1.0-2.5 parts by weight; The S5 is a capping agent, which contains a group that can react with isocyanate at the process temperature, including one or more of aliphatic primary or secondary monoamines, alicyclic primary or secondary monoamines, and amino alcohols containing both amino groups and hydroxyl groups, 0.01-1.0 parts by weight, preferably 0.02-0.5 parts by weight; The S7 is a catalyst; The S8 is an organic solvent.

[0010] Furthermore, the method for preparing the prepolymer 2 in step 1 comprises the following steps: 1) Component S1, component S2, and component S7 are mixed uniformly and reacted at 75-85°C for 2-6h until the NCO% of the system reaches the theoretical value to obtain an isocyanate-terminated prepolymer; 2) The isocyanate-terminated prepolymer system obtained in step 1 is cooled to 50°C, and then component S8 is added to dissolve and dilute, followed by component S6, reacting at 30-45°C for 5-20min, and then component S5 is added, and the reaction is continued at 30-45°C for 5-20min to obtain prepolymer 2.

[0011] Furthermore, the mixed system of components S1, S2 and S7 in step 1 includes S8; component S6 in step 2 is added to the system in the form of an aqueous solution, and the mass of water is 4-6 times the mass of component S6; component S5 is added to the system in the form of an aqueous solution, and the mass of water is 5-7 times the mass of component S5.

[0012] Further, the S1 is a polyisocyanate, including one or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate and dicyclohexylmethane diisocyanate, 8.0-20.0 parts by weight, preferably 10.0-18.0 parts by weight; The S2 is a macromolecular polyol having an average molecular weight of 500-5000 g / mol, including one or more of polyethylene glycol, polytetrahydrofuran ether glycol, polycaprolactone diol, polycarbonate diol, polyethylene adipate diol, polybutylene adipate diol, polyneopentyl adipate diol, and polyhexanediol adipate diol, in an amount of 68.0-85.0 parts by weight, preferably 70.0-85.0 parts by weight; The S5 is a capping agent, which contains a group that can react with isocyanate at the process temperature, including one or more of aliphatic primary or secondary monoamines, alicyclic primary or secondary monoamines, and amino alcohols containing both amino groups and hydroxyl groups, 0.01-1.0 parts by weight, preferably 0.02-0.5 parts by weight; The S6 is a chain extender, including one of ethylenediamine, hydrazine hydrate, piperazine, and isophoronediamine, preferably ethylenediamine, 0.5-4.0 parts by weight, preferably 1.0-2.5 parts by weight; The S7 is a catalyst; The S8 is an organic solvent.

[0013] The second technical solution of the present invention is to provide an aqueous polyurethane dispersion, which is a core-shell structured nanoparticle, wherein the shell is composed of a hydrophilic prepolymer 1, and the core is composed of a hydrophobic prepolymer 2, and the prepolymer 1 has hydroxyl groups on the main chain, and the hydroxyl groups are distributed on the surface of the nanoparticles; the solid content is 40-55wt%; and the average particle size of the solid content is 130-300nm, preferably 150-230nm.

[0014] Furthermore, the solid content of the aqueous polyurethane dispersion is 40-55 wt %, preferably 43-48 wt %; the average particle size of the solid content thereof is 130-300 nm, preferably 140-200 nm.

[0015] The third technical solution of the present invention is to provide an application of an aqueous polyurethane dispersion in adhesives. The aqueous polyurethane adhesive of the present invention may be a two-component formulated adhesive. The aqueous polyurethane adhesive comprises the aqueous polyurethane dispersion as described above or the aqueous polyurethane dispersion prepared by the preparation method as described above, and an auxiliary agent. The auxiliary agent may be an additive commonly used in the art for preparing aqueous adhesives, for example, a thickener, a defoamer, a curing agent, a wetting agent, water, and the like.

[0016] In order to enable the hydroxyl groups on the polymer chain segments to fully and effectively participate in the later reactions and better integrate with the curing agent, we designed the particles of the latex to be hydrophilic polyurethane coated with hydrophobic polyurethane, so that as many hydroxyl groups as possible are distributed on the surface of the nanoparticles.

[0017] Beneficial effects of the present invention: The adhesive obtained from the aqueous polyurethane dispersion prepared by the present invention has a bulk strength of >63.17 N / mm 2 It has excellent heat resistance and moisture resistance. After curing at 25℃ for 72h, the debonding length within 0.5h is only 1mm. After curing at 25℃ for 72h, the time for the adhesive strip to completely debond in 95% humidity test is >168 hours. DETAILED DESCRIPTION

[0018] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.

[0019] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.

[0020] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0021] Example 1 Prepolymer 1: 10 parts by weight of polyethylene glycol, 20 parts by weight of polytetrahydrofuran ether diol, 38 parts by weight of polycaprolactone diol, 8 parts by weight of hexamethylene diisocyanate, 30 g of acetone, and 0.1 g of Bi1610, which have been vacuum dehydrated, are added to a 2L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture is stirred at 75°C for 2 hours until the NCO% of the system reaches 2.7%, thereby obtaining an isocyanate-terminated prepolymer; the system containing the prepolymer is cooled to 50°C, and 350 g of acetone is added to dissolve and dilute; then the temperature is lowered to 30°C, and an aqueous solution containing 0.5 parts by weight of hydroxyethylethylenediamine and 1 part by weight of A95 is added and stirred for 5 minutes, wherein the mass of water is 4 times the total mass of hydroxyethylethylenediamine and A95; then an aqueous solution containing 0.01 parts by weight of diethanolamine is added, wherein the mass of water is 5 times the mass of diethanolamine, and stirring is continued for 5 minutes.

[0022] Prepolymer 2: 10 parts by weight of polyethylene glycol, 20 parts by weight of polytetrahydrofuran ether diol, 38 parts by weight of polycaprolactone diol, 8 parts by weight of hexamethylene diisocyanate, 30 g of acetone, and 0.1 g of Bi1610, which have been vacuum dehydrated, are added to a 2L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture is stirred at 75°C for 2 hours until the NCO% of the system reaches 2.7%, thereby obtaining an isocyanate-terminated prepolymer; the system containing the prepolymer is cooled to 50°C, and 350 g of acetone is added to dissolve and dilute; then the temperature is lowered to 30°C, and an aqueous solution containing 0.5 parts by weight of ethylenediamine is added and stirred for 5 minutes, and the mass of water is 4 times that of ethylenediamine; then an aqueous solution containing 0.01 parts by weight of diethanolamine is added, and the mass of water is 5 times that of diethanolamine, and stirring is continued for 5 minutes.

[0023] Prepolymer 1 and prepolymer 2 were transferred into a dispersion barrel with a volume ratio of 1:1.2. After stirring for 2 minutes, 1172 g of water was added for shear dispersion to obtain a crude emulsion. After acetone was separated by vacuum distillation, the solid content was adjusted. An aqueous polyurethane dispersion was obtained, which had a solid content of 40 wt % and an average particle size of the solids of 130 nm.

[0024] Take 100g of the aqueous polyurethane dispersion emulsion, put it in a beaker, mark and number it, and add the following additives to each beaker (the amount of each additive is based on 100g of the emulsion): 0.2wt% wetting agent, 0.02wt% defoaming agent, 0.3wt% thickener, 5wt% isocyanate curing agent, stir well to obtain an adhesive.

[0025] Preparation of the test sample: Apply the prepared adhesive on a 2cm*100cm rubber strip with a double-sided adhesive of 100g / m2, dry it in an oven at 65℃ for 5min, press it at 0.2MPa for 1s, and get the test sample. Immediately test the peel strength with a tensile machine, 180°, and the tensile rate is 200mm / min to measure its initial adhesive strength. Test the peel strength of the test sample within 15min at 25℃, 180°, and the tensile rate is 200mm / min to measure its initial peel strength.

[0026] The prepared adhesive was formed into a film on the release paper with a wet film thickness of 750μm. After being applied, it was placed in an oven at 65 degrees Celsius for 5 minutes. After being cured at 25 degrees Celsius for 72 hours, the film strength was tested.

[0027] The prepared adhesive was applied on the substrate with a double-sided adhesive coating of 100 g / m2. After application, the adhesive was dried in an oven at 65°C for 5 min and pressed at 0.4 MPa for 10 seconds to obtain the test sample. After curing at 25°C for 72 h, the sample was tested at 180°, 120°C*1000g*0.5h, and the debonding length within 0.5h was measured to obtain its later heat resistance data.

[0028] After curing at 25°C for 72h, test the time it takes for the rubber strip to completely debond at 180°, 70°C*95% humidity*500g to obtain its later moisture and heat resistance data.

[0029] Example 2 Prepolymer 1: 20 parts by weight of vacuum dehydrated polycarbonate diol, 20 parts by weight of polyethylene adipate diol, 25 parts by weight of poly(1,4-butylene adipate diol), 20 parts by weight of isophorone diisocyanate, 30 g of acetone, 0.1 g of Bi1610 was added to a 2L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture was stirred at 78°C for 2.5 hours until the system NCO% reached 2.7% to obtain an isocyanate-terminated prepolymer; the system containing the prepolymer was cooled to 50°C, and 350g of acetone was added to dissolve and dilute; then the temperature was lowered to 35°C, and an aqueous solution containing 4 parts by weight of N-(2-hydroxypropyl)ethylenediamine and 5 parts by weight of A95 was added and stirred for 5 minutes, and the mass of water was 6 times the total mass of N-(2-hydroxypropyl)ethylenediamine and A95; then an aqueous solution containing 1 part by weight of diethanolamine was added and stirred for 10 minutes, and the mass of water was 7 times the mass of diethanolamine; Prepolymer 2: 20 parts by weight of polycarbonate diol, 20 parts by weight of polyethylene adipate diol, 25 parts by weight of polybutylene adipate diol, 20 parts by weight of isophorone diisocyanate, 30 g of acetone, and 0.1 g of Bi1610, which have been subjected to vacuum dehydration, are added to a 2L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture is stirred at 78°C for 2.5 hours until the NCO% of the system reaches 2.7%, thereby obtaining an isocyanate-terminated prepolymer; the system containing the prepolymer is cooled to 50°C, and 350 g of acetone is added to dissolve and dilute; the temperature is then lowered to 35°C, and an aqueous solution containing 4 parts by weight of hydrazine hydrate is added and stirred for 5 minutes, wherein the mass of the water is 6 times the mass of the hydrazine hydrate; an aqueous solution containing 1 part by weight of diethanolamine is then added and stirred for 10 minutes, wherein the mass of the water is 7 times the mass of the diethanolamine; Prepolymer 1 and prepolymer 2 were transferred into a dispersion barrel, the volume ratio of prepolymer 1 to prepolymer 2 was 1:0.6, and after stirring for 2 minutes, 862 g of water was added for shear dispersion to obtain a crude emulsion; after acetone was separated by reduced pressure distillation, the solid content was adjusted; and an aqueous polyurethane dispersion was obtained, which had a solid content of 46 wt % and an average particle size of the solid content of 200 nm.

[0030] The adhesive was prepared according to the adhesive preparation method described in Example 1, and then the relevant performance tests were performed according to the detection method described in Example 1. The obtained data are shown in Table 1.

[0031] Example 3 Prepolymer 1: 15 parts by weight of poly(neopentyl adipate) diol, 70 parts by weight of poly(1,6-hexane adipate) diol, 9 parts by weight of toluene diisocyanate, 6 parts by weight of diphenylmethane diisocyanate, 30 g of acetone, 0.1 g of Bi1610 was added to a 2L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture was stirred at 85°C for 6 hours until the NCO% of the system reached 2.64%, thereby obtaining an isocyanate-terminated prepolymer; the system containing the prepolymer was cooled to 50°C, and 350g of acetone was added to dissolve and dilute; then the temperature was lowered to 45°C, and an aqueous solution containing 4 parts by weight of hydroxyethylethylenediamine and 5 parts by weight of A95 was added and stirred for 20 minutes, wherein the mass of the water was 6 times the total mass of the hydroxyethylethylenediamine and A95; then an aqueous solution containing 1 part by weight of diethanolamine was added and stirred for 20 minutes, wherein the mass of the water was 7 times the mass of the diethanolamine; Prepolymer 2: 10 parts by weight of poly(neopentyl adipate) diol, 70 parts by weight of poly(1,6-hexane adipate) diol, 9 parts by weight of toluene diisocyanate, 6 parts by weight of diphenylmethane diisocyanate, 30 g of acetone, and 0.1 g of Bi1610, which have been vacuum dehydrated, are added to a 2L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture is stirred at 85°C for 6 hours until the NCO% of the system reaches 2.7%, thereby obtaining an isocyanate-terminated prepolymer; the system containing the prepolymer is cooled to 50°C, and 350 g of acetone is added to dissolve and dilute; the temperature is then lowered to 45°C, and an aqueous solution containing 4 parts by weight of isophorone diamine is added and stirred for 20 minutes, wherein the mass of the water is 5 times the mass of the isophorone diamine; an aqueous solution containing 1 part by weight of diethanolamine is then added and stirred for 20 minutes, wherein the mass of the water is 6 times the mass of the diethanolamine; Prepolymer 1 and prepolymer 2 were transferred into a dispersion barrel, with the volume ratio of prepolymer 1 to prepolymer 2 being 1:1.2. After stirring for 2 minutes, 525 g of water was added for shear dispersion to obtain a crude emulsion. After acetone was separated by vacuum distillation, the solid content was adjusted. An aqueous polyurethane dispersion was obtained, which had a solid content of 55 wt % and an average particle size of the solid content of 300 nm.

[0032] The adhesive was prepared according to the adhesive preparation method described in Example 1, and then the relevant performance tests were performed according to the detection method described in Example 1. The obtained data are shown in Table 1.

[0033] Example 4 Prepolymer 1: 75 parts by weight of poly(1,6-hexanediol adipate) diol, 17 parts by weight of dicyclohexylmethane diisocyanate, 30 g of acetone, and 0.1 g of Bi1610 that have been subjected to vacuum dehydration treatment are added to a 2L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture is stirred at 85°C for 6 hours until the NCO% of the system reaches 2.7%, thereby obtaining an isocyanate-terminated prepolymer; the system containing the prepolymer is cooled to 50°C, and 350 g of acetone is added to dissolve and dilute; then the temperature is lowered to 45°C, and an aqueous solution containing 3 parts by weight of hydroxyethylethylenediamine and 4 parts by weight of A95 is added and stirred for 20 minutes, wherein the mass of the water is 6 times the total mass of the hydroxyethylethylenediamine and A95; then an aqueous solution containing 1 part by weight of diethanolamine is added and stirred for 20 minutes, wherein the mass of the water is 7 times the mass of the diethanolamine; Prepolymer 2: 75 parts by weight of poly(1,6-hexanediol adipate) diol, 17 parts by weight of dicyclohexylmethane diisocyanate, 30 g of acetone, and 0.1 g of Bi1610 that have been subjected to vacuum dehydration treatment are added to a 2L four-necked round-bottom flask equipped with a nitrogen inlet and outlet, and the mixture is stirred at 85°C for 6 hours until the NCO% of the system reaches 2.7%, thereby obtaining an isocyanate-terminated prepolymer; the system containing the prepolymer is cooled to 50°C, and 350 g of acetone is added to dissolve and dilute; then the temperature is lowered to 45°C, and an aqueous solution containing 4 parts by weight of piperazine is added and stirred for 20 minutes, wherein the mass of the water is 5 times the mass of the piperazine; then an aqueous solution containing 1 part by weight of diethanolamine is added and stirred for 20 minutes, wherein the mass of the water is 6 times the mass of the diethanolamine; Prepolymer 1 and prepolymer 2 were transferred into a dispersion barrel with a volume ratio of 1:1. After stirring for 2 minutes, 525 g of water was added for shear dispersion to obtain a crude emulsion. After acetone was separated by vacuum distillation, the solid content was adjusted. An aqueous polyurethane dispersion was obtained, which had a solid content of 55 wt % and an average particle size of the solids of 280 nm.

[0034] The adhesive was prepared according to the adhesive preparation method described in Example 1, and then the relevant performance tests were performed according to the detection method described in Example 1. The obtained data are shown in Table 1.

[0035] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the hydroxyethylethylenediamine in prepolymer 1 is replaced by ethylenediamine.

[0036] The adhesive was prepared according to the adhesive preparation method described in Example 1, and then the relevant performance tests were performed according to the detection method described in Example 1. The obtained data are shown in Table 1.

[0037] Comparative Example 2 The difference between Comparative Example 1 and Example 1 is that 0.5 parts by weight of ethylenediamine is added to prepolymer 1, and prepolymer 2 is not present in the reaction system.

[0038] The adhesive was prepared according to the adhesive preparation method described in Example 1, and then the relevant performance tests were performed according to the detection method described in Example 1. The obtained data are shown in Table 1.

[0039] Table 1 Performance test results of each test sample Compared with Examples 1-4, the adhesive obtained by the dispersion of Comparative Example 1 has low body strength, poor heat resistance in the later stage, and significantly reduced moisture and heat resistance in the later stage; compared with Examples 1-3, the adhesive obtained by the dispersion of Comparative Example 2 has low body strength, poor heat resistance in the later stage, and significantly reduced moisture and heat resistance in the later stage; compared with Comparative Example 1, the heat resistance and moisture and heat resistance of Comparative Example 2 are slightly improved in the later stage. The reason for this is that the introduction of hydroxyl groups on the polymer chain segments can increase the crosslinking degree and molecular weight when reacting with the curing agent in the later stage. The use of hydrophilic-hydrophobic polymer mixed emulsification to self-assemble into hydrophilic-hydrophobic nanoparticles on the outside makes the hydroxyl groups on the polymer chain segments distributed on the particle surface as much as possible, which can be better integrated with the curing agent, further improving the crosslinking degree and molecular weight of the polymer, thereby greatly improving its heat resistance and moisture and heat resistance in the later stage. The above comparative information proves that adding hydroxyl-containing polyamine and adopting a mixed emulsification process to prepare waterborne polyurethane can greatly improve the bulk strength and later heat resistance and moisture and heat resistance of the adhesive, thereby proving the rationality of the present invention.

[0040] Although the embodiments of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments.

Claims

1. A method for preparing an aqueous polyurethane dispersion, characterized in that: The following steps are involved: The prepolymer 1 and the prepolymer 2 are uniformly mixed to obtain a mixed solution, wherein the volume ratio of the prepolymer 1 to the prepolymer 2 is 1:1.2-1:0.6; The main chain of the prepolymer 1 has a hydroxyl group, and the prepolymer 2 is hydrophobic; Add water to the mixed solution and disperse by shearing; The organic solvent is separated and the solid content is adjusted to obtain a waterborne polyurethane dispersion with a core-shell structure that is hydrophobic inside and hydrophilic outside.

2. The preparation method according to claim 1, characterized in that: Step 1 The method for preparing the prepolymer 1 comprises the following steps: Component S1, component S2, component S7 are mixed uniformly and reacted at 75-85 ° C for 2-6h until the system NCO% reaches the theoretical value to obtain an isocyanate-terminated prepolymer; The system of the isocyanate-terminated prepolymer obtained in step 1 is cooled to 50° C., and then component S8 is added to dissolve and dilute, followed by adding components S3 and S4, reacting at 30-45° C. for 5-20 min, and then adding component S5, and continuing to react at 30-45° C. for 5-20 min to obtain prepolymer 1.

3. The preparation method according to claim 2, characterized in that: In step 1, the mixed system of components S1, S2 and S7 includes S8; in step 2, components S3 and S4 are added to the system in the form of aqueous solution, and the mass of water is 4-6 times the sum of the masses of components S3 and S4; component S5 is added to the system in the form of aqueous solution, and the mass of water is 5-7 times the mass of component S5.

4. The preparation method according to claim 2, characterized in that: The S1 is a polyisocyanate, including one or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate and dicyclohexylmethane diisocyanate, 8.0-20.0 parts by weight; The S2 is a macromolecular polyol having an average molecular weight of 500-5000 g / mol, including one or more of polyethylene glycol, polytetrahydrofuran ether glycol, polycaprolactone diol, polycarbonate diol, polyethylene adipate diol, polybutylene adipate diol, polyneopentyl adipate diol, and polyhexanediol adipate diol, in an amount of 68.0-85.0 parts by weight; The S3 is a hydrophilic compound containing an ionic group or a potential ionic group, which contains at least one group capable of reacting with isocyanate, including one or more sulfonic acid type hydrophilic compounds, 1.0-5.0 parts by weight; The S4 is a polyamine small molecule chain extender containing at least one or more hydroxyl groups, including one of N-(2-hydroxypropyl)ethylenediamine and hydroxyethylethylenediamine, 0.5-4.0 parts by weight; The S5 is a capping agent, which contains a group that can react with isocyanate at the process temperature, including one or more of aliphatic primary or secondary monoamines, alicyclic primary or secondary monoamines, and amino alcohols containing both amino groups and hydroxyl groups, 0.01-1.0 parts by weight; The S7 is a catalyst; The S8 is an organic solvent.

5. The preparation method according to claim 1, characterized in that: The method for preparing the prepolymer 2 in step 1 comprises the following steps: Component S1, component S2, component S7 are mixed uniformly and reacted at 75-85 ° C for 2-6h until the system NCO% reaches the theoretical value to obtain an isocyanate-terminated prepolymer; The system of the isocyanate-terminated prepolymer obtained in step 1 is cooled to 50° C., and then component S8 is added to dissolve and dilute, followed by adding component S6, reacting at 30-45° C. for 5-20 min, and then adding component S5, and continuing to react at 30-45° C. for 5-20 min to obtain prepolymer 2.

6. The preparation method according to claim 5, characterized in that: In step 1, the mixed system of components S1, S2 and S7 includes S8; in step 2, component S6 is added to the system in the form of an aqueous solution, and the mass of water is 4-6 times the mass of component S6; component S5 is added to the system in the form of an aqueous solution, and the mass of water is 5-7 times the mass of component S5.

7. The preparation method according to claim 5, characterized in that: The S1 is a polyisocyanate, including one or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate and dicyclohexylmethane diisocyanate, 8.0-20.0 parts by weight; The S2 is a macromolecular polyol having an average molecular weight of 500-5000 g / mol, including one or more of polyethylene glycol, polytetrahydrofuran ether glycol, polycaprolactone diol, polycarbonate diol, polyethylene adipate diol, polybutylene adipate diol, polyneopentyl adipate diol, and polyhexanediol adipate diol, in an amount of 68.0-85.0 parts by weight; The S5 is a capping agent, which contains a group that can react with isocyanate at the process temperature, including one or more of aliphatic primary or secondary monoamines, alicyclic primary or secondary monoamines, and amino alcohols containing both amino groups and hydroxyl groups, 0.01-1.0 parts by weight; The S6 is a chain extender, including one of ethylenediamine, hydrazine hydrate, piperazine, and isophoronediamine, 0.5-4.0 parts by weight; The S7 is a catalyst; The S8 is an organic solvent.

8. An aqueous polyurethane dispersion prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The aqueous polyurethane dispersion is a nanoparticle with a core-shell structure, wherein the shell is composed of a hydrophilic prepolymer 1, and the core is composed of a hydrophobic prepolymer 2. The main chain of the prepolymer 1 has hydroxyl groups, which are distributed on the surface of the nanoparticle. The solid content of the aqueous polyurethane dispersion is 40-55 wt %, and the average particle size of the solid content is 130-300 nm.

9. Use of the aqueous polyurethane dispersion as claimed in claim 8 in adhesives.

Citation Information

Patent Citations

  • A waterborne polyurethane adhesive and its preparation method

    CN114133533B

  • Waterborne polyurethane-polyurea dispersoid, preparation method thereof, single-side-sizing waterborne polyurethane adhesive and application of single-side-sizing waterborne polyurethane adhesive

    CN116199851A